A Analytical Study on Strength Characteristics of RC Buildings Subjected to Seismic Forces: Analyzing the seismic safety assessment methods for RC buildings (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Most existing RC buildings, especially older ones, lack sufficient resistivity to earthquakes. When these buildings are identified, they can be upgraded to withstand future earthquakes. The estimation of the seismic safty of existing buildings is a expensive and lengthy process. Simplified techniques may be justified in most structures. The objective of this paper is to review these simplified methods for the seismic safety assessment of existing buildings. The methods available are either qualitative or analytical or they combine both. These procedures depend on conditional evaluation visual-inspection and non - destructive testing. The analytical methods include capacity demand method, analysis push-over, inelastic time history analysis, etc. Another way of classifying the methods into three categories-Procedure level-1consisting of rapid visual screening. Level 2 procedures involving a simplified assessment of vulnerability based on information obtained from Level 1 structural drawings or site measurements. Level 3 involves detailed assessments of vulnerability using a computer. the city Hyderabad was under Seismic Zone- I up to 2002 and after that it was in Zone II as per IS1893. All the buildings constructed before and after will be checked in accordance with latest seismic code of India and compare A Results obtained from the proposed method with the results obtained from Seismic Coefficient method as per IS-1893 using ETABS and Pushover analysis using SAP-2000 as per ATC (Applied Technology Council).